A New Reality: The Role of Simulated Learning Activities in Postgraduate Psychology Training Programs - Paparo, Josephine; Beccaria, Gavin; Canoy, Doreen; Chur-Hansen, Anna; Conti, Janet E.; Correia, Helen; Dudley, Amanda; Gooi, Chien; Hammond, Sabine; Kavanagh, Phillip S.; Monfries, Melissa; Norris, Kimberley; et al. (Frontiers in Education, 2021)
In training to become a registered psychologist in Australia, as with many other countries, there is a requirement for students to attend placements, where they work with clients in an apprenticeship model under the guidance of qualified supervisors. In the context of COVID-19, tertiary sector psychology educators responsible for facilitating these placements, which typically require face-to-face client work, have been challenged to arrange or maintain practica. During the pandemic, across Australia, most placements have been affected through cancellation, postponement, or modification (e.g., using telehealth, supported by the Australian Federal Government). In this paper we describe a collaborative initiative by members of the psychology profession across 15 institutions of Australian postgraduate professional training programs. The initiative aimed to identify ways in which to develop and innovate psychological placement offerings, specifically using simulation-based learning. Although simulation-based learning in psychology training programs in Australia is a widely employed pedagogy for the scaffolding of theory into psychological practice, there is paucity of clear and comprehensive guidelines for the use of simulation to both optimize competency-based training and ensure public and student safety. The overarching aim of the group, and the focus of this paper, is to provide standardized guidelines for the inclusion of simulation-based learning in psychology training in Australia both during and post-COVID 19. Such guidelines may be equally valuable for psychology training programs globally.